USING GAMIFICATION IN DEVELOPING STUDENTS' CREATIVE COMPETENCE (Multidisciplinary Journal of Science and Technology, 2024)
This text provides a comprehensive overview of the evolution of gamification in education, particularly its application in developing students' creative competence. It traces the historical development of gamification from its early emergence in non-game contexts to its integration into educational software and digital games. The discussion highlights key milestones, such as the expansion of digital games in the 2000s and the popularization of gamification in the early 2010s. It emphasizes the recent shift towards using gamification specifically to foster creativity, detailing various strategies and benefits associated with this approach. Additionally, the text acknowledges ongoing research into the effectiveness of gamification and identifies potential drawbacks that educators should consider when implementing gamified activities.